Two new Canthocamptidae (Copepoda, Harpacticoida) from sponges of the Kara and Laptev Seas - Novikov, Aleksandr; Sharafutdinova, Dayana (Zootaxa, 2021)
We studied copepods washed off the sponges from two Arctic seas: the Kara and the Laptev. We found new species in families Miraciidae, Canthocamptidae Brady, 1880, Argestidae, and Ectinosomatidae. We describe two new species of the Canthocamptidae Brady, 1880. Heteropsyllus spongiophilus sp. nov. from the Kara Sea, differs from its congeners in the armament of the swimming legs and the maxilliped. Mesopsyllus glacialis sp. nov. from the Laptev Sea, can be distinguished by the legs armament, its sexual dimorphism and the 7-segmented female antennules.